2013
DOI: 10.17221/6917-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of different central nervous system depressors combined with ketamine for anaesthesia in mice

Abstract: ABSTRACT:The aim of this study was to compare some depressors of the central nervous system combined with ketamine in order to find an adequate scombination for anaesthesia in mice, coupled with a simple, easy to use and reliable method. Forty Swiss OF-1 mice (Mus musculus), 20 females and 20 males with a body weight from 35 to 45 g aged from 12 to 16 weeks, were used to evaluate one of the following central nervous system depressors (CNSD): acepromazine (5 mg/kg), diazepam (5 mg/kg), medetomidine (1 mg/kg), m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
(25 reference statements)
1
1
1
Order By: Relevance
“…These observations are in contrast to data obtained in mice by Serrano et al (2013) who reported that female mice lost PWR earlier than males in response to treatment with α 2 -agonists. However, the rats did not lose the pedal reflex after treatment with the acepromazine and midazolam combinations.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…These observations are in contrast to data obtained in mice by Serrano et al (2013) who reported that female mice lost PWR earlier than males in response to treatment with α 2 -agonists. However, the rats did not lose the pedal reflex after treatment with the acepromazine and midazolam combinations.…”
Section: Discussioncontrasting
confidence: 99%
“…Consequently, only the combination of α 2 -agonists and ketamine seems to be adequate at these doses for use as an anaesthetic because it reduces pain perception, as previously reported by other authors (Cruz et al 1998;Arras et al 2001). Similar to other authors, we did not observe an increase of diuresis (side-effect of α 2 -agonists), nor salivary secretion (Cruz et al 1998;Serrano-Caballero et al 2013). …”
Section: Discussionsupporting
confidence: 92%
“…Anesthesia for small rodents is commonly performed through the injection of one, or a mixture of parenteral agents [ 1 3 ]. The intraperitoneal (IP) route of administration is often utilized for laboratory mice when there is an inability to use inhalant anesthesia for research-specific requirements, lack of inhalational anesthesia equipment, or due to technical limitations of intravenous or intramuscular injections in small species [ 4 ].…”
Section: Introductionmentioning
confidence: 99%